DETERMINATION OF SELECTED PARAMETERS THAT INFLUENCE PLANTING SPACE UNIFORMITY ON MAIZE SEED - Ahmed, K.; Saleh, Aminu; Musa, A. D.; Kalu, G. (FUDMA JOURNAL OF SCIENCES, 2023)
In order to realize optimum plant population for profitable maize production, there is to obtain uniform plant spacing. The objective of this study was, therefore, to determine certain planting parameters that influence uniformity in plant-to-plant and row-to-row spacing. To achieve this, a 4-row animal-drawn planter was used to plant SAMMAZ 14 maize variety in the Experimental Farm of Ahmadu Bello University, Zaria. Treatment factors varied were hopper seed quantity with three levels: 25, 50 and 100 %, three levels of ground speed: 0.6, 0.8, and 1 m/s, and two levels of planting depth: 1.5 and 2.5 cm. Results obtained shows that the multiple index, miss index, feed index and precision index were seen to be affected by planting speed with the best multiple, miss and precision index were achieved at planting speed of 0.8 m/s except for feed index whose best value was achieved at 1 m/s. Similarly, multiple and precision index were both affected by seed hopper quantity but no effect on Miss and Feed index. It was also observed that the best mean values were obtained at 100 % seed hopper quantity. All the indexes were never affected by planting depth while the performance of the planter on seed uniformity indexes improve with moderate planting speed and increasing seed quantity in the hopper. Therefore, planting at 0.8 m/s planting speed and 100 % seed hopper full result in uniform crop establishment for a profitable crop production.
Keywords: Ground Speed; Plant Population; Planting Depth; Precision Index; Spacing Uniformity